2007
DOI: 10.1038/sj.bjc.6603732
|View full text |Cite
|
Sign up to set email alerts
|

Combination treatment with Grb7 peptide and Doxorubicin or Trastuzumab (Herceptin) results in cooperative cell growth inhibition in breast cancer cells

Abstract: Grb7 has potential importance in the progression of cancer. We have previously identified a novel peptide that binds to the SH2 domain of Grb7 and inhibits its association with several different receptor tyrosine kinases. We have synthesised the Grb7 peptide, G7-18NATE, with two different cell penetrating peptides, Penetratin and Tat. In this study, we have shown that both Penetratin-and Tat-conjugated G7-18NATE peptides are able to inhibit the proliferation of SK-BR-3, ZR-75-30, MDA-MB-361 and MDA-MB-231 brea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
79
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(81 citation statements)
references
References 24 publications
1
79
1
Order By: Relevance
“…This is further corroborated by preclinical models, which have shown that a Grb7 peptide inhibitor in combination with Herceptin treatment enhances the inhibitory effect on the proliferation of SKBR3 cells and inhibit the proliferation of MDA-MB-361 cells. 32 Taken together, these findings suggest that HER2 may not be the sole oncogene in this amplicon.…”
Section: Discussionmentioning
confidence: 73%
“…This is further corroborated by preclinical models, which have shown that a Grb7 peptide inhibitor in combination with Herceptin treatment enhances the inhibitory effect on the proliferation of SKBR3 cells and inhibit the proliferation of MDA-MB-361 cells. 32 Taken together, these findings suggest that HER2 may not be the sole oncogene in this amplicon.…”
Section: Discussionmentioning
confidence: 73%
“…Pero et al (46) identified a novel peptide that binds to the SH2 domain of Grb7 and inhibits its association with receptor tyrosine kinases. The proliferation of various breast cancer cell lines was impaired by treatment with Grb inhibitors, including an inhibitor of Grb10.…”
Section: Discussionmentioning
confidence: 99%
“…RTKs are among the most critical targets for tumor therapy, and studies have been employed to inactivate RTKs as an effective strategy to enhance the chemosensitivity (19,20). Met overexpression and subsequent activation is correlated with tumor invasive growth, so it was tested that whether the sensitivity of Met-expressing tumor cells toward chemotherapeutic drugs could be modulated by the Met inhibition.…”
Section: Tctpmentioning
confidence: 99%
“…Various studies have shown that inactivation of RTKs such as ErbB2 (19) or other important functioning proteins such as Grb7 (20) can significantly enhance the chemosensitivity. Here, a novel peptide-based sensitizer specifically targeting the Met inactivation was supposed to be investigated.…”
Section: Introductionmentioning
confidence: 99%